The presentation of gladiatorial spectacles in the Greek East: Roman culture and Greek identity - Carter, Michael J.D. (My University, 1999)
Once believed by many to offer the historian little of value beyond a horrifying, if titillating, glimpse into the Roman psyche, gladiatorial combat is now appreciated as an important expression of Roman cultural priorities. Gladiatorial combat presented the spectator with examples of the key, martial values at the heart of what it meant to be a Roman: skill with arms in actual combat with an opponent, extreme courage in the face of mortal danger, and the rigid discipline necessary to fight and even die in the quest for victory. Since the Roman sense of cultural identity was based to a high degree on shared values and on participation in the same moral universe, gladiatorial combat, which presented in a spectacular and exemplary way many of these fundamental mores , helped in the construction and maintenance of Roman sense of cultural identity. Throughout the Roman world, the presentation of gladiatorial combats went hand-in-hand with the process of Romanization as different groups of people adopted aspects of Roman culture and a sense of Roman identity. But little seems to have changed in the Greek East as a result of Roman conquest and rule. The main exception to this general rule is the prevalence and popularity of gladiatorial combats. This dissertation considers the significance of this key Roman spectacle in Greek society and its impact on Greek culture. The presentation of Roman gladiatorial combat by Greeks for Greeks in the Greek cities of the East was an attempt to locate Roman culture within a Greek civic and ceremonial context. But the values present in gladiatorial combat are the same values at the heart of traditional Greek culture: the values of the gladiator are essentially those of a heroic champion, who fought in single combat to win glory and fame in victory.
Keywords: Classics; Classics